Temporary Mental Nerve Paresthesia Originating from Periapical Infection - Ozgur Genc Sen; Volkan Kaplan (Case Reports in Dentistry)
Many systemic and local factors can cause paresthesia, and it is rarely caused by infections of dental origin. This report presents a case of mental nerve paresthesia caused by endodontic infection of a mandibular left second premolar. Resolution of the paresthesia began two weeks after conventional root canal treatment associated with antibiotic therapy and was completed in eight weeks. One year follow-up radiograph indicated complete healing of the radiolucent periapical lesion. The tooth was asymptomatic and functional.